Republic of Azerbaijan : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Azerbaijan. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Azerbaijan's real GDP growth accelerated to 31 percent in 2006, driven by rapidly increasing oil production and transportation. Non-oil real GDP, excluding oil and gas transportation, grew by about 8 percent, as nontradable sectors benefited from ramped up government spending and rapidly growing banking credit. Inflation rose into the double digits by August 2006. Progress in other structural reforms has been mixed. The short-term growth and external outlooks remain exceptionally favorable, but keeping inflation from increasing further represents a major challenge.